FUSARIUM WILT CAUSED BY FUSARIUM OXYSPORUM AND ITS PATHOGENESIS IN LAVANDULA ANGUSTIFOLIA (Ustozlar uchun, 2026)
Fusarium oxysporum is a soil-borne filamentous fungus that causes Fusarium wilt disease in numerous economically important plant species worldwide. Although it has been extensively studied in agricultural crops, its interaction with medicinal and aromatic plants such as Lavandula angustifolia remains insufficiently investigated. This study is aimed at understanding the pathogenic mechanisms of F. oxysporum by integrating molecular, anatomical, and physiological processes occurring in lavender plants. Through comparative analysis of specialized forms and host–pathogen interaction models, the sequential stages of pathogen colonization, host tissue responses, and the development of systemic dysfunction are identified. Furthermore, the study provides a broader perspective on lavender pathogenesis within the context of Fusarium disease and highlights existing knowledge gaps for future molecular investigations.